2014
DOI: 10.1039/c4fo00537f
|View full text |Cite
|
Sign up to set email alerts
|

On characterization of anisotropic plant protein structures

Abstract: In this paper, a set of complementary techniques was used to characterize surface and bulk structures of an anisotropic Soy Protein Isolate (SPI)-vital wheat gluten blend after it was subjected to heat and simple shear flow in a Couette Cell. The structured biopolymer blend can form a basis for a meat replacer. Light microscopy and scanning electron microscopy provided a detailed view of structure formation over the visible surfaces of the SPI-gluten blend. Protein orientation in the direction of the flow was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 9 publications
1
51
0
Order By: Relevance
“…Those requirements are derived from studies in which shear-induced structure formation was studied using model systems (Manski et al, 2007a;Sprakel et al, 2008;Van Loon et al, 2014;Vermant, 2001). We have applied this principle to dense biopolymer blends, for example a blend that contained soy protein isolate (SPI) and vital wheat gluten (WG) (Grabowska et al, 2014;Krintiras et al, 2014Krintiras et al, , 2015. Here, the phase-separation was induced by blending two incompatible biopolymers.…”
Section: Discussionmentioning
confidence: 99%
“…Those requirements are derived from studies in which shear-induced structure formation was studied using model systems (Manski et al, 2007a;Sprakel et al, 2008;Van Loon et al, 2014;Vermant, 2001). We have applied this principle to dense biopolymer blends, for example a blend that contained soy protein isolate (SPI) and vital wheat gluten (WG) (Grabowska et al, 2014;Krintiras et al, 2014Krintiras et al, , 2015. Here, the phase-separation was induced by blending two incompatible biopolymers.…”
Section: Discussionmentioning
confidence: 99%
“…Soy concentrate and wheat gluten have been reported to form fibrous structures under shear flow (Grabowska, Tekidou, Boom, & van der Goot, 2014;Krintiras, Gobel, Bouwman, van der Goot, & Stefanidis, 2014). The presence of two separate biopolymeric phases is generally thought to be needed for structure formation.…”
Section: Outlook On the Development Of Solid Meat-like Structuresmentioning
confidence: 99%
“…In other work (Krintiras et al, ) the Couette Cell was used with free gluten powder. The sheared mixtures had a composition like that in Table , but without the hydrogel component and with more salt.…”
Section: Resultsmentioning
confidence: 99%
“…The κ‐carrageenan particles did release the gluten and fibrilization occurred to a much larger extent during the shearing process. However, while comparing the structure sheared from the particles with the structures obtained after shearing the original mixture without particles (Krintiras et al, ), it was observed that although fibrilization occurs, it is much less than with the original mixture. The macrostructure of the meat analog is not yet well developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation